2014
DOI: 10.3109/01612840.2013.853332
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Symptoms of Postpartum Traumatic Stress in a Sample of Mothers with Preterm Infants

Abstract: Objective There are no established screening criteria to help identify mothers of premature infants who at risk for symptoms of emotional distress. The current study, using data obtained from recruitment and screening in preparation for a randomized controlled trial, aimed to identify potential risk factors associated with symptoms of depression, anxiety and posttraumatic stress in a sample of mothers with premature infants hospitalized in a neonatal intensive care unit. Method 135 mothers of preterm infants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
4
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 37 publications
0
33
4
4
Order By: Relevance
“…In a recent study of mothers of premature infants (N=135), investigators found that maternal sociodemographic factors as well as the infant's physiologic stability did not contribute to early identification of postpartum traumatic stress in the Neonatal Intensive Care Unit (NICU). 2 These findings differ slightly from another study of parental stress (N=100) in the NICU, in that older parents and interruption of breast feeding plans were associated with higher stress levels but not necessarily postpartum traumatic stress.…”
Section: Introductioncontrasting
confidence: 56%
See 1 more Smart Citation
“…In a recent study of mothers of premature infants (N=135), investigators found that maternal sociodemographic factors as well as the infant's physiologic stability did not contribute to early identification of postpartum traumatic stress in the Neonatal Intensive Care Unit (NICU). 2 These findings differ slightly from another study of parental stress (N=100) in the NICU, in that older parents and interruption of breast feeding plans were associated with higher stress levels but not necessarily postpartum traumatic stress.…”
Section: Introductioncontrasting
confidence: 56%
“…The fact that 24.1% of the infants were admitted to the NICU with only three NICU stays 7 days or longer suggests that this sample does not represent the very low birth weight infants described in research that associates post-traumatic stress experiences with families that take up to a year to mend. 2,5 Because the results of this study illustrate a lasting, unresolved stress for all families with infants admitted to the NICU (r=.88), one must question how even the short stays in the NICU result in similar emotions. The longitudinal Swedish study of Hildingsson and Thomas may offer some answers; these researchers found that even if a woman perceived her pregnancy, birth or transition home as stressful, regardless of actual circumstances, which this stress lasted up to one year.…”
Section: Discussionmentioning
confidence: 99%
“…In relation to the prevalence of depressive symptoms among caregivers of NBIs hospitalized in the NICU, prior studies reported a 10-59% prevalence. 1,6,7,9,12,19 In our population, the prevalence was close to the lower limit of this range in both measurements.…”
Section: Discussionmentioning
confidence: 85%
“…Parents of preterm babies report more perceived stress and experience more adjustment difficulties and need for support during the first year after delivery compared to parents of infants born at term (7,8). It has been documented that parents may experience severe psychological distress, such as posttraumatic stress reactions and depression following the preterm birth of their baby, which subsequently may impact on the mother-infant-interactions and their attachment relationship (9)(10)(11)(12)(13)(14). In turn, poorer parenting competencies, such as lack of sensitivity during interactions may affect the infant's development (15).…”
Section: Introductionmentioning
confidence: 99%